PENAMBAHAN DISPERSING AGENT PADA PROSES PASCA TANNING UNTUK MENGURANGI KADAR COD (Chemical Oxygen Demand) - Sofwan Siddiq Abdullah; Renita Wahyu Meydasari; Swatika Juhana; Fadzkurisma Robbika (Politek ATK Yogyakarta Press, 2025)
In the leather tanning industry, post-tanning process generates liquid waste. One of the parameters of liquid waste is Chemical Oxygen Demand (COD). The chemicals used in the post-tanning process have an impact on COD levels of the wastewater. The purpose of this study is to investigate the addition of a dispersing agent during the post-tanning stage to reduce the Chemical Oxygen Demand (COD) content in the process effluent. Based on the stages of post-tanning, the fatliquoring fixation process contains a large amount of organic substances, which is indicated by the high COD value. The higher the COD, the lower the dissolved oxygen content in water. Elevated COD levels can have adverse impacts on the environment. The method used in this study was a trial involving the addition of a dispersing agent during the post-tanning process. COD measurements were carried out using a UV-Vis spectrophotometer. The addition of 10% dispersing agent reduced COD levels from 62,200 mg/L to 56,550 mg/L (reduction of 9.08%). The results of the experiment demonstrate that the addition of a dispersing agent in the post-tanning process can reduce the wastewater treatment load in the leather tanning industry.